Experiences and Challenges of Implementing the Individualized Education Plan (IEP) for Students with Learning and Intellectual Disabilities in Kuwait - Alhajeri, Ohoud Nasser (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
This study explores the development and effectiveness of Individualized Education Programs (IEPs) in supporting students with special educational needs (SEN). Utilizing a descriptive-analytical approach, the research examines key factors influencing the implementation of IEPs, including teacher expertise, parental involvement, and institutional support. The study sample comprises special education teachers and school administrators, selected using a stratified sampling method to ensure diverse representation. Findings indicate that while IEPs play a crucial role in enhancing student learning outcomes, challenges persist in adapting the curriculum, facilitating interdisciplinary collaboration, and assessing continuous progress. The study also reveals that teachers with specialized training in inclusive education demonstrate greater confidence in designing and executing IEPs, whereas limited parental engagement and administrative constraints hinder effective implementation. The results underscore the need for comprehensive professional development programs, stronger family-school partnerships, and policy reforms to optimize IEP practices. These findings offer valuable insights for educators, policymakers, and stakeholders seeking to improve inclusive education strategies and individualized instructional planning.